Ordovician gastropods from Argentina - Beresi, Matilde Sylvia (2001)
Ordovician (Arenig to Lower Llanvirn) gastropods are summarized from the San Juan Formation, in the San Juan Precordillera of Argentina. Preservation is poor, but at least fourteen genera representing bellerophontoids, macluritoids, euomphaloids, pleurotomaroids, murchisonoids, and an onychochiloid are present. The San Juan Formation is the only known Ordovician occurrence of the superfamilies Macluritoidea and Onychochiloidea in South America.